Neutron diffraction and short range ordering study in multiferroic Bi2Fe4O9. (20th March 2019) - Singh, A K; Mohapatra, S R; Khare, Preeti; Ganguli, Nirmal; Wildes, A; Siruguri, V; Kaushik, S D
Abstract: We present the evidence of room temperature short range ordering (SRO) in the Cairo pentagonal lattice type Bi2 Fe4 O9 (BFO) using neutron diffraction study. The signature of this SRO is observed in the form of a broad diffuse magnetic peak at Q ∼ 1.3 Å −1 in the neutron diffraction pattern at room temperature. A transition from SRO into a long range magnetic order is observed in subsequent low temperature neutron diffraction patterns, which corresponds to a magnetic ordering regime arising from local spin arrangements of Fe ions. At T = 2 K, magnetic moments for Fe1 (octahedral) and Fe2 (tetrahedral) atoms are 3.78 ± 0.16 μ B and 3.37 ± 0.13 μ B, respectively. The nature of SRO at room temperature is found to be magnetic as determined from detailed polarized neutron diffraction experiment. Substantial variation in the lattice parameters, O–Fe–O bond angles, Fe–O bond lengths and the effective magnetic moment per Fe-site near Néel temperature (TN ) is evidenced post neutron diffraction analysis. To further apprehend the origin of SRO, first principle calculation is explored and is correlated with structural as well as superexchange mechanisms of BFO.